Schwannoma of the uterine cervix: a rare case report - Biswajit Dey; Sairem Mangolnganbi Chanu; Jaya Mishra; Evarisalin Marbaniang; Vandana Raphael (Korean Society of Obstetrics and Gynecology, 2019)
Schwannomas are neurogenic tumors, which are among the most varied tumors with respect to morphology, clinical associations, and presentations; they occur in a wide variety of sites. The uterine cervix is a rare site of occurrence and only 15 cases of schwannomas of the uterine cervix, including 5 benign and 10 malignant cases, have been reported to date. Thus, schwannomas of the uterine cervix may pose diagnostic difficulty. Here, we report a case of benign schwannoma of the uterine cervix in a 37-year-old female, who presented with vaginal spotting.